Fluorescence enhancement mediated by high-index-faceted Pt nanocrystals: roles of crystal structures. Issue 16 (7th February 2018) - Liu, Shuo; Cao, Shuo-Hui; Tian, Na; Xiao, Chi; Zhou, Zhi-You; Chen, Zhong; Li, Yao-Qun; Sun, Shi-Gang
Abstract : High-index structures, especially step atoms, contribute in enhancing fluorescence signals. Abstract : In this work, we report studies that focus on correlating fluorescence enhancement with crystal structures, using Pt nanoparticles as a demonstration. Both experimental and theoretical calculation results provide evidence to support an interesting phenomenon that high-index structures, especially step atoms, contribute in enhancing fluorescence signals.